Publications from clinical trials: Process, conflict of interest and the evidence base - Binns, Colin; Low, W. (2013)
Objectives: The aim of this study is to review the issues of publication of clinical trials with consideration of ethics and the incomplete evidence base. Methods:We review clinical trials and issues of communications and ethics. Several case studies of notable public health researchers will be discussed. Results:Many of the major breakthroughs of public health practice, including the works of John Snow would not have been published under modern guidelines for scientific communication. The research-publication system of modern health care poses many challenges for editors. Journal editors need to include a balance of different types of studies where insufficient randomised controlled trials are available. Conclusion:Clinical trials are a reliable source of evidence for health care practitioners. Journals need to uphold the integrity of the information provided by randomised controlled trials (RCTs) and synthesise and communicate health information. At the same time, editors must assess non-RCT evidence and be vigilant for many of the other potential problems in health and medical communication. © 2013 Elsevier Inc.